Do middle classes bring institutional reforms? - Norman Loayza; Jamele Rigolini; Gonzalo Llorente (Institute for the Study of Labor (IZA), 2012)
We revisit the link between poverty, the middle class and institutional outcomes using a newly developed cross-country panel dataset containing detailed information on the distribution of income and expenditures. When the size of the middle class increases (measured as the proportion of people with income above 10 US Dollars a day in PPP terms), social policy on health and education becomes more active and the quality of governance regarding democratic participation and official corruption improves. This does not occur at the expense of economic freedom, as an expansion of the middle class also implies more market-oriented economic policy on trade and finance. The impact of a larger middle class appears to be more robust than those of lower poverty, lower inequality, or higher GDP per capita.
urn:nbn:de:101:1-201207125637
Keywords: D3; H5; O1; O4; 330; poverty; middle class; income; institutions; development; Mittelschicht; Armut; Einkommensverteilung; Staatliche Einflussnahme; Institutioneller Wandel; Welt